A comparative analysis of inflation-adjusted and historical cost accounting information: Implications for the value relevance of corporate reports - Orits Frank Ebiaghan (Trends Economics and Management, 2019)
Purpose of the article: This study investigates the effect of historical cost accounting on the reported profit of a company, with an evaluation of current cost accounting as an alternative reporting method in a high-inflationary and volatile economy as experienced in Nigeria. Using secondary data gleaned from the annual reports and accounts of ten (10) manufacturing companies quoted in the industrial sector of consumer goods of the Nigerian Stock Exchange from 1996-2016. Methodology/methods: To test the formulated hypotheses, a multiple regression model was formulated comprising the depreciation charge, taxes and dividend as the independent variables while reported profits both at historical and current cost of the firm served as the dependent variables. The Ordinary Least Square (OLS) estimation technique was employed to ascertain the inter-relationships between the variables. Scientific aim: This research is aimed at empirically investigating, by means of available statistics, the effect of historical cost accounting on the reported profit of a company during period of inflation. Findings: The study revealed that both historical cost and current cost accounting have significant effect on reported profit, as an increase in the depreciation charge, tax bills and dividends declared by firms will occasion a decrease in the reported profit. Conclusions: It is recommended that companies should prepare their financial reports using both historical cost and fair value (current cost) methods simultaneously, as this will allow the companies to ascertain the true financial position of their companies before declaring dividends and other benefits.
Keywords: M40; M41; M49; 650; inflation accounting; current cost (fair-value accounting); profit; dividend; depreciation; historical cost